Infections Caused by Carbapenem-Resistant Enterobacteriaceae: An Update on Therapeutic Options - Sheu, Chau-Chyun; Chang, Ya-Ting; Lin, Shang-Yi; Chen, Yen-Hsu; Hsueh, Po-Ren (Frontiers in Microbiology, 2019)
Carbapenems are considered as last-resort antibiotics for the treatment of infections caused by multidrug-resistant gram-negative bacteria. With the increasing use of carbapenems in clinical practice, the emergence of carbapenem-resistant pathogens now poses a great threat to human health. Currently, antibiotic options for the treatment of carbapenem-resistant Enterobacteriaceae (CRE) are very limited, with polymyxins, tigecycline, fosfomycin, and aminoglycosides as the mainstays of therapy. The need for new and effective anti-CRE therapies is urgent. Here, we describe the current understanding of issues related to CRE and review potential therapeutic strategies for CRE infections, including high-dose tigecycline, high-dose carbapenem, double carbapenem, and combination therapies. We also review the newly available antibiotics which will play important roles in the future treatment of CRE infections: ceftazidime/avibactam, which is active against KPC and OXA-48 producers, and meropenem/vaborbactam, which is active against KPC producers. Although direct evidence for CRE treatment is still lacking and the development of resistance is a concern, these antibiotics provide promising therapeutic options for CRE infections. Finally, we review other potential anti-CRE antibiotics in development: plazomicin, imipenem/relebactam, cefiderocol, and eravacycline. Currently, high-dose and combination strategies should be considered in severe CRE infections to maximize treatment success. In the future, when more treatment options are available, therapy for CRE infections should be individualized and based on molecular phenotypes of resistance, susceptibility profiles, disease severity, and patient characteristics. More high-quality studies are needed to guide effective treatment for infections caused by CRE.